Effect of Non-ionic Surfactant on the Structural and Dielectric Properties of Polypyrrole. (2015) - Batool, Aisha; Kanwal, Farah; Riaz, Saira; Atiq, Shahid; Naseem, Shahzad
Abstract: This work reports successful formation of polypyrrole by chemical oxidation method in the presence of different weight percentages of non-ionic surfactant (0-4%) dispersed during polymerization of pyrrole at 0 °C. Structural changes in these surfactant effected PPy samples were investigated by fourier transform infrared spectroscopy (FT-IR) and dielectric measurements taken in the range of 1 KHz to 1 MHz at 300k. Dielectric properties of all the composites obeyed power law and increased linearly with the loading weight percentage of non-ionic surfactant.